Survival of a mixed culture of microencapsulated probiotic strains against the gastrointestinal barrier in vitro - Luz Alba Caballero–Pérez; Rene Tejedor–Arias; Elaysa Josefina Salas–Osorio (Revista Científica, 2023)
Encapsulating materials preserve the viability of probiotics under gastrointestinal conditions. The aim of the research was to evaluate the protective effect of an encapsulating matrix, composed for the first time with three prebiotic materials to maintain the viability of a mixed culture of spray–dried microencapsulated probiotics under simulated gastrointestinal and prebiotic conditions. Microcapsules of four formulations with better viability were then evaluated by inoculating microencapsulated and free strains in MRS broth, adjusting three pH values, bile salts, broth with and without carbohydrate (prebiotic test), incubated at 36 ± 1°C / 24 h; then the percentage of post–treatment cell survival was calculated. Showing that, formulation 1 presented higher barrier protection with average counts: 7.31 log CFU·g-1 lactobacilli and 7.75 log CFU·g-1 (Saccharomyces boulardii) / 4 h (SGF), reaching 6.78 log CFU·g-1 in the four formulations (SIF) with a higher average survival rate 79.79% and 85.06% SGF and SIF, in vitro. On the other hand, the prebiotic test maintained average counts of 9.40 log CFU·g-1 (Lactobacillus spp.) and 6.99 log CFU·g-1 (S. boulardii) / 24 h. The protection exerted by the microspheres under simulated gastrointestinal and prebiotic conditions at therapeutic levels (≥ 106 CFU·mL-1) was demonstrated.